Efektivitas Media Pembelajaran Animasi Powtoon Terhadap Peningkatan Hasil Belajar Kognitif Siswa Sekolah Dasar - Nur DS, Yulistina; Sadiah, Tia Latifatu; Suparman, Tarpan; Prawiyogi, Anggy Giri; Damayanti, Ririn (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – In the world of education, learning media has a very important role to increase the enthusiasm of students during the learning process. However, the limited media available in schools is one of the problems, thus encouraging teachers to create innovative and creative learning media independently. The purpose of this study was to determine the effect of using powtoon animation video-based learning media on cognitive learning outcomes of elementary school students.Method – This study used quantitative research methods with a pre-experimental research design of one group pretest-posttest. The research sample was fifth grade students totaling 35 students. The location of this research was SDN Dawuan Barat I in the 2023/2024 school year. The data analysis technique employed requires test analysis. The data analysis technique employs prerequisite analysis in the form of validity, reliability, normalcy, and homogeneity tests, whereas the hypothesis test employs the independent sample t-test.Findings – The result of this study indicate the effect of media use. Based on the results of research and data analysis, it can be concluded that the use of powtoon animated video media has an influence on students' cognitive learning outcomes in class V IPAS subjects at SDN Dawuan Barat I. This can be seen in hypothesis testing using paired sample t test calculation obtained Sig value. This can be seen in hypothesis testing using the calculation of paired sample t test obtained Sig. (2-tailed) of 0.000, because 0.000 <0.05 then Ho is rejected, and Ha is accepted. Thus, proving that the use of powtoon animated video media has an effect on students' cognitive learning outcomes in IPAS subjects. Research Implications – Cognitive learning outcomes of primary school students can be improved by using powtoon animation video-based media in IPAS learning in class IV at SDN Dawuan Barat I Cikampek.